Allogeneic adipose-derived stem cells regenerate bone in a critical-sized ulna segmental defect. Issue 13 (July 2016) - Wen, Congji; Yan, Hai; Fu, Shibo; Qian, Yunliang; Wang, Danru; Wang, Chen
Adipose-derived stem cells (ASCs) with multilineage potential can be induced into osteoblasts, adipocytes and chondrocytes. ASCs as seed cell are widely used in the field of tissue engineering, but most studies either use autologous cells as the source or an immunodeficient animal as the host. In our present study, we explored the feasibility of applying allogeneic ASCs and demineralized bone matrix (DBM) scaffolds for repairing tubular bone defects without using immunosuppressive therapy. Allogeneic ASCs were expanded and seeded on DBM scaffolds and induced to differentiate along the osteogenic lineage. Eight Sprague–Dawley (SD) rats were used in this study and bilateral critical-sized defects (8 mm) of the ulna were created and divided into two groups: with ASC-DBM constructs or DBM alone. The systemic immune response and the extent of bone healing were evaluated post-operatively. Twenty-four weeks after implantation, digital radiography (DR) testing showed that new bones had formed in the experimental group. By contrast, no bone tissue formation was observed in the control group. This study demonstrated that allogeneic ASCs could promote bone regeneration and repair tubular bone defects combined with DBM by histologically typical bone without systemic immune response